2005
DOI: 10.1038/sj.tpj.6500319
|View full text |Cite
|
Sign up to set email alerts
|

Only low levels of exogenous N-acetyltransferase can be achieved in transgenic mice

Abstract: Therapeutic and environmental aromatic amines and hydrazines are substrates for the arylamine N-acetyltransferases (NAT). In all, 10 transgenic lines containing either the human NAT1 or NAT2 transgene were developed using multiple promoters. The presence of the transgene was confirmed by determining copy number, mRNA and enzyme activity. Despite some lines having high copy numbers of the transgene, only modest or no increases in enzymatic activity could be found in a variety of tissues. The NAT1 transgene coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 37 publications
2
14
0
1
Order By: Relevance
“…The mouse albumin enhancer/promoter has been shown to direct efficient liver-specific transgene expression (Pinkert et al, 1987) and was chosen because we found it to drive expression of a luciferase reporter in HepG2 cells more effectively than the endogenous human NAT2 promoter. We identified only one viable founder animal, which was found to contain a single copy of the transgene, consistent with previous attempts by others to generate NAT transgenic mice in which only low-copy founders were identified and/or lethality was observed (Cao et al, 2005). It has been postulated that overexpression of human NAT transgenes, particularly human NAT1, may be detrimental dur- tg Nat1/2(Ϫ/Ϫ) female mouse.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The mouse albumin enhancer/promoter has been shown to direct efficient liver-specific transgene expression (Pinkert et al, 1987) and was chosen because we found it to drive expression of a luciferase reporter in HepG2 cells more effectively than the endogenous human NAT2 promoter. We identified only one viable founder animal, which was found to contain a single copy of the transgene, consistent with previous attempts by others to generate NAT transgenic mice in which only low-copy founders were identified and/or lethality was observed (Cao et al, 2005). It has been postulated that overexpression of human NAT transgenes, particularly human NAT1, may be detrimental dur- tg Nat1/2(Ϫ/Ϫ) female mouse.…”
Section: Discussionsupporting
confidence: 73%
“…Another human NAT2 transgenic mouse model, constructed using the cytomegalovirus promoter, yielded only a 2-fold increase in NAT activity for isoniazid (Cao et al, 2005). Studies attempting to express human NAT1 in transgenic mice have succeeded in producing only low levels of expression, suggesting that high levels of human NAT1 either alone or in combination with endogenous mouse Nat2 activity may be detrimental to the animal .…”
Section: Sugamori Et Almentioning
confidence: 99%
“…Mice engineered with constructs designed to drive overexpression of (HUMAN)NAT1 exhibit poor survival and the progeny of the few surviving founders only exhibit small increases in hepatic pABA acetylation [32], [33], suggesting that (HUMAN)NAT1 overexpression during development could be harmful, possibly due to disruption of folate homeostasis. Moreover, the overexpression of (HUMAN)NAT1 in mice provokes NTDs usually associated with folate deficiency [32], [34], [35] and has complex effects on the incidence and severity of orofacial clefting [33].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the overexpression of (HUMAN)NAT1 in mice provokes NTDs usually associated with folate deficiency [32], [34], [35] and has complex effects on the incidence and severity of orofacial clefting [33].…”
Section: Introductionmentioning
confidence: 99%
“…
Aims To determine whether increased N-acetyltransferase (NAT) activity might have a toxic effect during development and an influence on folate levels since previous work has shown that only low levels of exogenous NAT can be achieved in constitutionally transgenic mice (Cao, et al, 2005)
Main Methods A human NAT1 tet-inducible construct was used that would not be expressed until the inducer was delivered. Human NAT1 cDNA was cloned into pTRE2 and injected into mouse oocytes.
…”
mentioning
confidence: 99%